Strengthening Literacy for Strengthening the social impacts of the Covid-19 pandemic - Mustofa, Mukhlis (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Covid-19 became one of the biggest epidemics that changed the economic, political, social and cultural structure. All countries on this earth experienced this epidemic, but the attitude was different and efforts to overcome the impact of the epidemic in Indonesia have not shown positive developments and experienced symptoms of social rejection from the community. The main problem facing this pandemic is why the condition of the socio-cultural environment of the Indonesian people responding to co-19 is difficult to control with science. Efforts to Strengthen Literacy Means of strengthening the social impact of the pandemic can begin with the optimization of social media in socializing the impact of the pandemic. Another supporting element of strengthening during this era is that the principle of example has not yet fully emerged in overcoming this disease. Covid-19 as a global pandemic is a very clear example of the impact of globalization. As a global problem, this requires a response that is also global without prejudice to social handling. Keywords ; pendemic covid-19, optimization of social media